Effect of the time to antivenom administration on recovery from snakebite envenoming-related coagulopathy in French Guiana. - Stéphanie Houcke; Jean Marc Pujo; Segolene Vauquelin; Guy Roger Lontsi Ngoula; Severine Matheus; Flaubert NkontCho; Magalie Pierre-Demar; José María Gutiérrez; Dabor Resiere; Didier Hommel; Hatem Kallel (Public Library of Science (PLoS), 2023)
Background Snakebite (SB) envenoming is an acute emergency requiring an early care delivery. We aimed to search for the time to reach healthcare facilities in various regions of French Guiana (FG) and to assess the impact of time to antivenom (AV) on the correction of coagulation parameters in these patients. Methodology This is a prospective observational study conducted in Cayenne General Hospital between January 1st, 2016, and July 31st, 2022. We included all patients hospitalized for SB envenoming less than 48h after the bite, and receiving antivenom (AV). We assessed the time lapse between SB and medical attention and the time needed to return of the coagulation parameters to normal. Principal findings Overall, 119 patients were investigated, and 48.7% were from remote areas. The median time from SB to AV therapy was 09:15 h (05:32-17:47). The time was longer in patients from remote rural locations. AV was dispensed within the first six hours after the SB in 45 cases (37.8%). Time from SB to reaching normal plasma fibrinogen concentration was 23:27 h (20:00-27:10) in patients receiving AV≤6h vs. 31:23 h (24:00-45:05) in those receiving AV>6h (p<0.001). Whereas, the time from AV administration to reach normal fibrinogen dosage was similar in the two groups. Conclusions Patients from rural settings in FG suffer from a delay in AV administration after SB envenoming leading to an extended time in which patients are coagulopathic. Once AV is administered, clotting parameters recover at a similar rate. Supplying remote healthcare facilities with AV and with medical teams trained on its use should be planned.